Growth performance and phytochemicals of Vernonia amygdalina Delile as affected by light intensity, growing media, harvest time and storage duration - A. Bakar, Nursuhaili (2019)
Vernonia amygdalina Del., locally known as pokok bismillah, is a potential herb with high medicinal value for the cure of many types of human ailments. It is found grown in a variety of habitats, causing wide variation in the growth performance and phytochemical content. In this regard, a field experiment and two laboratory experiments were conducted at Department of Crop Science, Faculty of Agriculture, Universiti Putra Malaysia. The objectives of the study were to evaluate the effects of light intensity and suitable growing media on growth, physiology and biomass yield of V. amygdalina. The treatments for the field experiment comprised of three levels of light intensity (30%, 50% and 100% that equivalent to open field) and four types of growing media (soil, cocopeat, empty fruit bunch (EFB) and burnt paddy husk (BPH). Seedlings were raised in a nursery and transferred to the field at 4 weeks after propagated. Plants were harvested at 18 weeks after transplanted (WAT) to the field. Results indicated that V. amygdalina grown under 50% light intensity in EFB growing medium had the highest biomass yield (490 kg ha-1) with a greater plant height (182 cm), number of branches (3 branches), stem diameter (22 mm), root surface area (3631 cm) and photosynthesis rate (22.6 μmol CO2 m-2s-1) among the treatments imposed. Experiment 2 was carried out to determine the suitable harvest time for optimum phytochemical contents in V. amygdalina leaves. Leaves samples from plants grown at the optimum requirement of the light intensity and growing media on V. amygdalina (50% light intensity, EFB) obtained from Experiment 1 were used in this study. The experiment comprised of six treatments of different harvest time (3, 6, 9, 12, 15 and 18 WAT). Results revealed that total phenolic content obtained were 91 and 84 mg GAE/g DW in leaf samples of plants harvested at 9 and 18 WAT, respectively. Similar pattern was found on total flavonoid content where it showed an increment from 3 to 9 WAT, then decreased sharply at week 12 but rising again until 18 WAT. Antioxidant activity (DPPH radical scavenging activity) was high from plants harvested at 9, 15 and 18 WAT. As harvest time increased the total chlorophyll content and plant nutrients content tended to increase. Heavy metals content were below the permissible limits of World Health Organization (WHO). Experiment 3 was carried out to quantify the phytochemical contents of dried V. amygdalina leaves at different storage durations. The experiment consisted of seven treatments of different storage durations (0, 3, 6, 9, 12, 15 and 18 weeks). The results showed the 12-week storage duration of dried leaves of V. amygdalina achieved high stability of phytochemicals of total phenolic and flavonoid contents. There were decreases of 44% and 58% of total phenolic and flavonoid contents for 18-week storage duration, respectively. The nutrient content also decreased until 18 weeks of storage. However, V. amygdalina could be as a great source of nitrogen, potassium and magnesium since the contents were above the recommended daily allowance (RDA) set by WHO. Therefore, V. amygdalina is suitable to be harvested at 18 WAT in order to get the optimum phytochemicals content with minimum heavy metal contamination as well as high in biomass yield. Heavy metal contents and microbial contamination were at tolerable levels as they were below the permissible limits prescribed by WHO. Thus, V. amygdalina dried leaves were considered safe to be consumed until 18 weeks of storage.